Changes in clearance, volume and bioavailability of immunosuppressants when given with HAART in HIV‐1 infected liver and kidney transplant recipients. (12th September 2013) - Frassetto, Lynda; Floren, Leslie; Barin, Burc; Browne, Matthew; Wolfe, Alan; Roland, Michelle; Stock, Peter; Carlson, Laurie; Christians, Uwe; Benet, Leslie
ABSTRACT: Solid organ transplantation in human immunodeficiency virus 1 (HIV)‐infected individuals requiring the concomitant use of immunosuppressants (IS) [e.g. cyclosporine (CsA) or tacrolimus (TAC)] and antiretrovirals (ARVs) [e.g. protease inhibitors (PIs) and/or non‐nucleoside reverse transcriptase inhibitors (NNRTIs)] is complicated by significant drug interactions. This paper describes the pharmacokinetics of CsA and TAC in 52 patients on both IS and NNRTIs, PIs or combined NNRTIs + PIs, in studies conducted at 2 weeks, 3, 6, 12 and 24 months after transplantation. Cyclosporine and TAC blood concentrations were measured by LC/MS/MS. This multisubject, varied ARV–IS drug combination, longitudinal observational patient study provided a unique opportunity to examine the effect of different ARV drugs on IS pharmacokinetics (PK) by comparing the ratios of parameters over time and between PK parameters. Subjects taking concomitant PIs exhibited increases in CsA and TAC exposure ( AUC /dose) due to the increased apparent oral bioavailability and decreased apparent oral clearance. Those subjects taking CsA and concomitant efavirenz (EFV) showed time dependent increases in exposure due to 30% increases in the apparent oral bioavailability over time as well as a decreased apparent oral clearance, while subjects on TAC and EFV showed time‐dependent changes in all PK parameters. The increased bioavailability was not observed in patients on CsA and nevirapine (NVP). These differences between IS drugs and the changes in PK parameters are not easily predicted, illustrating the importance of continued therapeutic drug monitoring in patients on these complex medication regimens. Published 2013. This article is a U.S. Government work and is in the public domain in the USA.